Recycling of waste plastics into fuels. LDPE conversion in FCC - Passamonti, Francisco Javier (2012)
In order to study the tertiary recycling of waste polymers in standard FCC units low density polyethylene (LDPE) was dissolved into a commercial vacuum gas oil at 2 and 6 wt.% and converted over two equilibrium FCC catalysts of the octane-barrel and resid types in a CREC Riser Simulator laboratory reactor. The reaction temperatures were 500, 525 and 550 ◦C, the mass catalyst to oil relationship was 6.35 and the contact times were from 3 to 30 s. The study included the effect of the concentration of LDPE over conversion, the various product (dry gas, LPG, gasoline, LCO and coke) yields and selectivities. Results were very similar for the two concentrations. At typical conversions of 70 wt.%, dry gas and gasoline yields increased about 10 wt.%, LPG yields between 9 and 13 wt.%, LCO yields decreased more than 15 wt.% and coke yields were lower than 7.7 wt.% The RON index of gasoline was improved slightly (up to one point), mainly due to significant increases in olefin concentrations, while the fuel quality of the LCO cut was not affected. LDPE is easily converted and seems to be subjected to primary reactions of catalytic cracking, thus increasing the yields of olefins in the LPG and gasoline boiling ranges. It was concluded that recycling waste LDPE by co-processing it as part of conventional feeds to the FCC would not interfere with the standard operation.